Application of Aloe Vera Compress to Reduce Body Temperature of Post-Op Patients Submandibular Abscess Drainage Incision with Hyperthermia Nursing Problems in the Children's Ward of Raden Mattaher Hospital, Jambi Province - Vitria; Sulistiawan, Andika (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
One of the symptoms of submandibular abscess is hyperthermia due to increased white blood cells. One non-pharmacological treatment that can be used to treat fever in children is a warm compress. There are also other compress methods that can be used, namely with the traditional plant Aloevera or what is commonly known as aloe vera. The aim of this case study is to provide an overview of giving aloe vera compresses to reduce the body temperature of children with a nursing diagnosis of hyperthermia. The case study was carried out for 3 days by providing nursing care to patients with hyperthermia nursing problems using observation techniques, interviews, literature studies, and administering aloe vera compresses based on Evidence Based Nursing. From the implementation, the results showed that after being given the aloe vera compress, the patient's body temperature decreased, namely on the first day the temperature before implementation was 39.40C and after the implementation, the temperature dropped to 390C. on the second day before being given the implementation the body temperature was 37.80C and after giving the implementation the body temperature dropped to 37.30C. The conclusion from this case study was that the nursing evaluation showed that there was a decrease in the patient's body temperature after being given the implementation of aloe vera compress.